Developing running economy in triathlonists using explosive-strength training - Kivimäki, A. (University of Jyväskylä, 2021)
Triathlon is a demanding three event multisport (swim, bike, run). In competitions, avoiding total fatigue is most challenging during the run. Improving running economy is one way to ensure better endurance and results. Running economy can be improved by endurance, strength, and sprint training, which result in improvements in aerobic, anaerobic, and neuromuscular power and capacity. The purpose of this study was to investigate with novel triathlon exercise test how explosive-strength training affects running economy after biking. An 8-week training intervention included explosive-strength training 2 times a week combined. Exercises included traditional barbell exercises, e.g squat, deadlift, and bench press. Focus was to train with barbell and multi-joint moves to gain full load to the neuromuscular system. Drop jumps and core exercises were also included. Novel race situation simulating maximal test, which combines WHO submaximal bicycle ergometer test, 2 minutes change time to maximal treadmill test was also developed. This test was performed before and after the exercise intervention with same bike load steps and treadmill speeds. Development was assessed by measurement of lactate levels and HR as well as analysis of changes in RPE. In treadmill lactate levels were significantly lower in end test. Average run lactate change was -17,8% ±7,5% (p < 0,05 in measuring points 4, 12 and 16 minutes). Running time was extended 03:22 ±01:59, 16,6% (p < 0,05). Peak treadmill speed development was 1,0 km/h to 14,2 km/h ±1,5 km/h, 7,6% (p < 0,05). Explosive-strength barbell weight training combined with drop jumping can significantly improve triathlon running economy. The novel triathlon maximal test gave important information to test persons how lactate levels behaved after bike.